Implementation of Energy Efficiency Based on Time Scheduling to Improve Network Lifetime in Wireless Body Area Network (WBAN) - ., Subono; Al Rasyid, M. Udin Harun; Astawa, I Gede Puja (EMITTER International Journal of Engineering Technology, 2015)
ZigBee applications of IEEE 802.15.4 Wireless Sensor Network (WSN) with Low Rate Wireless Personal Area Network (LR-WPAN) can be integrated with e-health technology Wireless Body Area Network (WBAN). WBAN are small size and can communicate quickly making it easier for people to obtain information accurately.WBAN has a variety of functions that can help human life. It can be used in the e-health, military and sports. WBAN has the potential to be the future of wireless communication solutions. WBAN use battery as its primary power source. WBAN has limited energy and must be able to save energy consumption in order to operate for a long time. In this study, we propose a method of time scheduling called cycle sleep period (CSP) as WBAN solutions to save energy and improve energy efficiency. The CSP method is implemented in the real hardware testbed using sensor e-health includes temperature body and current sensor. We compared the performance of CSP method with duty cycle management (DCM) time scheduling-based and without using time scheduling.From the measurement results, our proposed idea has decreasingenergy consumption.Keywords: WSN, LR-WPAN, WBAN, e-health, Time Scheduling